LITERATURE RIVIEW: EFEKTIFITAS RANGE OF MOTION (ROM) AKTIF TERHADAP PENINGKATAN KEKUATAN OTOT PADA PENDERITA STROKE - Nonok Karlina; Erida Fadila; Fega Nurpuji Khairiyah (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Introduction: Stroke sufferers really need good treatment to prevent physical and mental disability because stroke patients can recover completely and quickly handled within the first 6 hours (golden period), but if more than that time does not get maximum treatment then there will be disability and physical weakness such as hemipares. Objective: This literature summary aims to review the relationship between the effectiveness of active range of motion (ROM) on increasing muscle strength in stroke patients. Research method: In compiling this research literature researchers use the PIO method: Population is a stroke patient, Intervention with active ROM, Outcome muscle strength.Results: Based on 5 journals, it was found that there was an influence after Rangge Of Motion (ROM) therapy in healing stroke that experienced muscle weakness. Conclusion: ROM exercise is effective for increasing muscle strength and preventing muscle weakness, by giving exercise 2x a day morning and evening about 15-30 minutes.